Agnetti - a cent'anni da adesso = Agnetti - a hundred years from now - Meneguzzo, Marco 1954-; Agnetti, Germana; Barbato, Guido; Corà, Bruno 1942-; Nicolin, Paola; Pinkus, Karen 1963-; Re, Elena 1962-; Verzotti, Giorgio 1953- (Silvana editoriale, 2017)
Vincenzo Agnetti (Milan 1926-1981) was central to the international Conceptual Art scene in the 1960s: a poet, critic, and reciter, he followed his own path from the time of his friendship with Piero Manzoni and the Azimuth group. But it was in 1966/67 that he began to produce works such as the Bakelite axioms and the felt portraits and actions with their fundamental concepts of words, the territory, translation, relating, and the singularity and universality of communication. This book, edited by Marco Meneguzzo together with the Archivio Vincenzo Agnetti, and thanks to its numerous essays and its abundant photographic and technical information, is the most complete tool for getting to know an artist to whom the global art system is paying the tribute of a well-merited success. Exhibition: Palazzo Reale, Milan, Italy (04.07.-24.09.2017)
Catalog of an exhibition held at the Palazzo Reale, Milan, Italy, July 4-Sept. 24, 2017
Keywords: Agnetti, Vincenzo -- 1926-1981; Ausstellungskatalog -- Palazzo reale -- 04.07.2017-24.09.2017 -- Mailand; Bildband